The Performance of Non-pns Islamic Religious Exechers With Work Environment on Work Satisfaction of Employees of the Ministry of Religion Office in Kua Simokerto District, Surabaya City - Zarnuji, Aqib (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Everyone must desire to fulfill a sense of pleasure in it by showing that he is happy and satisfied with what he is doing. In the world of work, job satisfaction is very important for an employee; it will affect the attitude and morale of employees while carrying out their work. Job satisfaction is an individual thing and is influenced by various factors. Therefore, the institution must consider what factors make employees look happy. This study aims to determine how important the work environment is in increasing employee satisfaction. The method used in this research is a descriptive qualitative analysis using a case study research type by utilizing primary and secondary data sources. The results of this study indicate that the work environment has a positive influence on job satisfaction. If the quality of the work environment is good, then perceived satisfaction positively affects employee job satisfaction.